MUTU CABAI RAWIT (CAPSICUM FRUTESCENS L) PADA TINGKAT KEMATANGAN DAN SUHU YANG BERBEDA SELAMA PENYIMPANAN - Desi Natalia Edowai; Stella Kairupan; Handry Rawung (Agroindustrial Technology, University of Trunojoyo Madura, 2016)
The objective of this study is to know the ripeness level of small chilli and the right temperature during storage as far as the quality of small chilli can to defend until marketing. The study was conducted at the laboratory of Physiology and Postharvest and laboratory of Food Science and Technology of Research in Agriculture Faculty of Sam Ratulangi University Manado. Three level of ripeness are green ripe, green reddish ripe and red ripe. Temperature of storages are storage in room temperature 28°C – 32°C (64 – 77%), 4°C – 10°C (90 - 95%), 4°C – (-22)°C (95 – 98%), and –10°C (99%). With long storage are 30 days. The Method of analyzed study result is descriptive analysis and the dataare presented by the table. The quality of small chilli during storage looked about the height of water, weight, the height of capsaicin, and colour. The right temperature and the right ripeness can to maintain quality of small chilli until storage. The result study show is in level ripeness green ripe and green reddish ripe and than storage temperature 4°C – 10°C (90 - 95%) can maintain the qualiy of small chilli during storage. It is looked from amount of the height of water, weight, the height of capsaicin, and colour during storage always increase regulary.